Iron and vitamin interactions in marine diatom isolates and natural assemblages of the Northeast Pacific Ocean - Natalie R. Cohen; Kelsey A. Ellis; Wilton G. Burns; Robert H. Lampe; Nina Schuback; Zackary Johnson; Sergio Sañudo‐Wilhelmy; Adrian Marchetti (Limnology and Oceanography, 2017)
Trace metals and B‐vitamins play critical roles in regulating marine phytoplankton growth and composition. While some microorganisms are capable of producing certain B‐vitamins, others cannot synthesize them and depend on an exogenous supply. Therefore, external factors influencing vitamin synthesis, such as micronutrient concentrations, alter the extent to which B‐vitamins are available to auxotrophs in surface waters. We examined iron, B 7 (biotin) and B 12 (cobalamin) dynamics in diatoms through laboratory culture experiments and within natural diatom assemblages present along an iron gradient in the Northeast Pacific Ocean. In laboratory cultures of the diatom Pseudo‐nitzschia granii , biotin synthase (BIOB ) expression decreased 2‐fold under iron limitation, suggesting iron status may affect B 7 production in diatoms. Additionally in laboratory cultures of the diatom Grammonema cf. islandica , which contains a B 12 ‐independent methionine synthase ( METE ), a 15‐fold increase in the expression of METE was observed when grown in the absence of B 12 with no significant influence of iron status, suggesting METE expression can be driven by B 12 status alone. Iron and B‐vitamin amendment experiments with natural diatom assemblages in iron‐limited waters of the Northeast Pacific Ocean provide evidence for vitamin‐associated molecular responses that suggest elevated B 7 biosynthesis and the emergence of B 12 limitation following iron addition. Furthermore B‐vitamin gene modules comprised of partial and/or complete B‐vitamin biosynthetic pathways in diatoms increased in response to iron addition, including genes potentially involved in the processing of B 12 intermediates. Our results indicate that vitamins may play an important role in regulating phytoplankton growth and composition in this region, particularly following natural iron addition events.